Activating ZnO‐Based Hierarchical Particles for Visible Light Dependent Photocatalytic Performance via Cr‐Incorporated Rapid Chemical Synthesis. Issue 3 (31st October 2021) - Naeem, Hafiz Muhammad; Tariq, Salman; Moiz, Muhammad Abdul; Khan, Mahmood; Rehman, Nagina; Basit, Muhammad Abdul
Abstract: Flower like nanostructured ZnO hierarchical particles termed as NSPs exhibit high surface area as well as defect free growth which makes them competent for further exploration. In this work, a simple chemical approach to incorporate Chromium (Cr) as dopant in ZnO NSPs is utilized, ensuring the combined effect of effectual nature of pristine ZnO NSPs as well as visible light harvesting character owing to the Cr‐doping. Using a simple wet‐chemical approach, developed Cr‐doped ZnO NSPs are developed having appreciable nanostructure characterized by scanning electron microscopy, energy dispersive spectroscopy, UV–vis spectroscopy, and other relevant techniques. As affirmed by the change in the color of ZnO NSPs as well as reduction in the bandgap value ( E g ≈ 2.9 eV), ZnO NSPs exhibit significant increase in the photocatalytic degradation of Rhodamine B (RhB) dye that is taken as reference for determination of evolution of visible light dependent characteristics in ZnO NSPs. Nearly 70% degradation of RhB is obtained just in an hour which reflects the efficient photoactive behavior of Cr‐doped ZnO NSPs. Abstract : A simplistic wet‐chemical route for incorporating the Cr‐ions in non‐conventional, flower‐like morphology of ZnO is realized. Owing to the successful inclusion of Cr, ZnO exhibits enhanced visible light harvesting tendency that is utilized for degrading toxic industrial dye via photocatalysis.